An Investigation of Pedagogical Content Knowledge of Secondary School Mathematics Teachers in Relation with Triangle and Quadrilateral Concepts - Mehmet İhsan Yurtyapan, İlhan Karataş, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The purpose of this study is to investigate pedagogical content knowledge of secondary school mathematics teachers about triangles and quadrilaterals. In particular, it is focused on knowledge of content and students as two components of teachers' pedagogical content knowledge. In this study, case study was used as one of the types of qualitative research methods.. The sample is comprised of 12 secondary school mathematics teachers who are selected equally from the three groups, namely having teaching experience of 0-5 years, 6-10 years, and 11 and above years. Data is gathered by the use of 9 open-ended questions including different types of scenarios and semi-structured interviews in relation with triangle and quadrilateral concepts. The data is analyzed by the use of content analysis method Findings show that secondary school mathematics teachers' pedagogical content knowledge about triangles and quadrilaterals are not at the desired level in the component of content knowledge, whereas they are relatively better in the component of knowledge of students. Moreover, it was determined that teachers have similar misconceptions with secondary school students in triangle and quadrilateral concepts.